“Sandhigata Vata” A Disease Of Modern Era: A Conceptual Review - Prakash, Patel Satya; Sujata, Yadav (International Research Journal of Ayurveda & Yoga, 2021)
Shandhigatavata (Osteoarthritis) is a disease due to vitiated Vata in various sandhi or joints in the body. It is described under Vatavyadhi in almost every literature of Ayurveda. When the vitiated Vata increased, the dhatus (body tissues) undergoes Kshayaavatha. There is the role of many environmental, dietary, and lifestyle factors in the pathogenesis of Sandhigatavata (Osteoarthritis). All these factors lead to Vataprakopa and affect the individual health a lot. Sandhigatavata (Osteoarthritis) is the topmost disease of the modern era and becomes a challenging disease. It is the number one cause of disability in industrialized countries. In modern sciences, it is called osteoarthritis. Osteoarthritis is the most common joint disorder that begins in around the third decade of life asymptomatically and showed the symptoms mostly in old age. In recent decades, the disease occurrence starts early due to changing lifestyle and the disease affects women more than men. Osteoarthritis or degenerative arthritis is a degenerative joint disorder characterized by degeneration of joint cartilage and adjacent bone that can cause joint pain and stiffness. Since OA is the most commonly disturbing joint disease but still no permanent relief is available in modern sciences and the same is still under research works. In modern medical science, mainly analgesics, anti-inflammatory drugs or surgery are the options for the treatment of Osteoarthritis, which provide symptomatic relief, but also become the causative factor for adverse effects. So, the present review helps the understand the disease of the modern era through the ayurvedic approach and help in the integrative approach in the treatment of Sandhigatavata or osteoarthritis.